The effectivity of fentanyl versus tramadol as intravenous patient-controlled analgesia after cesarean section - (:unkn) unknown (My University, 2010)
Background. Patient-controlled analgesia (PCA) is the most widely used treatment method for post-cesarean section pain. Objectives. To compare two different opioids with respect to analgesic quality and side effects. Material and Methods. Sixty patients undergoing elective cesarean surgery were enrolled into two groups. Group F (n = 30) had postoperative IV PCA with fentanyl and Group T (n = 30) had IV PCA with tramadol. Postoperative pain scores, opioid requirements, side effects and patient satisfaction were compared. Results. The patient demographics were similar in both groups. Group F patients consumed 638.4 ± 179 μg of fentanyl, and Group T patients consumed 559.5 ±207 mg of tramadol. The number of patients requiring additional opioid was similar in both groups. Patient satisfaction did not differ in the two groups. Conclusions. Both fentanyl and tramadol provide sufficient postoperative analgesia and patient satisfaction when used in PCA. © Copyright by Wroclaw Medical University.
Keywords: Analgesia; Cesarean section; Fentanyl; Patient-controlled; Postoperative pain; Tramadol